The Applications and Complexity Analysis Based on Network Embedding Behaviors under Evolutionary Game Framework. (15th June 2020) - Su, Xin; Zhang, Hui; Guo, Shubing
Abstract : In this paper, we use the dynamic mechanism of biological evolution to simulate the enterprises' bounded rational game. We construct game models of network embedding behaviors of horizontal and vertical enterprises in supply chain, explain the repeated games of random pairs of enterprises by replication dynamic differential equations, study the characteristics and evolution trend of this flow, conduct simulation experiments, clarify the evolution direction and law of network embedding strategy selection of supply chain enterprises, and discuss the stable state of evolutionary game and its dynamic convergence process. The results show that the probability of supply chain enterprises choosing a network embedding strategy is related to the enterprises' special assets investment cost, cooperation cost, network income, and cooperation benefits. Supply chain enterprises should reduce the special assets investment cost and cooperation cost, maximize network income and cooperation income, narrow the gap between the extra-cooperation profit and the current cooperation profit, and restrain them from violating cooperation contracts or taking opportunistic actions.